The Effect of an Inquiry-Based Learning Model Grounded in Self-Determination Theory on Self-Efficacy and Academic Anxiety Among Elementary School Students in Lempuing Jaya - Edy Mawardi; Aprilia Tina Lidyasari (Journal of Educational Sciences, 2026)
Low self-efficacy and high academic anxiety remain common among elementary school students and may hinder the learning process. This study aims to analyze the effect of inquiry-based learning grounded in self-determination theory on students’ self-efficacy and academic anxiety. A quantitative approach with a quasi-experimental non-equivalent control group design was employed. The participants consisted of 46 fifth-grade students from two elementary schools in Lempuing Jaya, selected through purposive sampling. Data were collected using a validated and reliable Guttman scale questionnaire. Data analysis involved descriptive and inferential statistics, including independent sample t-test and MANOVA. The results revealed a significant increase in students’ self-efficacy and a decrease in academic anxiety, both partially and simultaneously. Quantitatively, self-efficacy increased by 32%, while academic anxiety decreased by 30.5% after the intervention. These findings indicate that fulfilling students’ basic psychological needs autonomy, competence, and relatedness contributes to improved psychological outcomes. Therefore, inquiry-based learning based on self-determination theory is an effective approach to enhance self-efficacy and reduce academic anxiety among elementary school students.